Etnowisata Desa Denai Lama: Kajian Antropologi Ekologi di Kecamatan Pantai Labu - Zahra, Maulida; Dora, Nuriza (Al-Hayat: Natural Sciences, Health & Environment Journal, 2024)
This research examines the ecology of rice fields in the Pantai Labu District. The community in the Pantai Labu District utilizes the ecology of rice fields not only as a food supplier but also as a tourist destination that can add value to the rice fields in the Pantai Labu District. The aim of this research is to describe how the community is able to increase the high value of the rice fields in Denai Lama Village, Pantai Labu District, Deli Serdang Regency. This research also discusses the culture and local wisdom in the Denai Lama Tourism Area and the activities that are characteristic of the culture and local wisdom in the Denai Lama Tourism Area, Deli Serdang Regency. The method used in this research is qualitative research with ethnographic methods. Data collection techniques include interviews, observations, and documentation. The research results state that Denai Lama Tourism Village is the first Tourism Village in Deli Serdang Regency, initiated by the Head of the Department of Youth, Sports, Culture, and Tourism of Deli Serdang Regency. This village is also considered one of the cleanest villages in Indonesia and has often received national awards. By utilizing the rice fields not only for food supply but also as a tourist destination, it adds value to the rice fields which has a significant impact on Denai Lama Tourism Village. The principle of this tourism village is more towards education, culture, culinary, making it an attraction for Denai Lama Village. This place is located on vast hectares of rice fields, with interesting photo spots for visitors. There are also many unique activities in Denai Lama Village, such as traditional culinary snacks, an annual folk festival, and a horse dance performance. Ethno-tourism in Denai Lama Village is a suitable title for research because it is one of the local wisdoms in North Sumatra, specifically in the Pantai Labu District, Deli Serdang Regency.